Athletic talent as a scientific problem and challenge for practice - Issurin, V. (Journal of Kinesiology and Exercise Sciences, 2019)
Aim. A narrative review of the research results of the multi-aspectual phenomenon of sports talent by researchers from various research centers around the world. Basic procedures. Analysis and synthesis in a narrative review of various methodological concepts regarding research on sports talent, with particular notice of selected American (USA), Canadian, Dutch, German (DDR) and Soviet (USSR) stances. Results. The commonly accepted approach presupposes the division of long-term preparation into a number of stages, at which various age and sport-specific tasks are solved, and young athletes overcome appropriate phases of their giftedness and talent evaluation. The objective difficulties in Talent Identification (TI) are associated with variations in the rate of maturation and unevenness of biological and sport-specific development of young prospects. Serious restrictions regarding early evaluation of giftedness and talent are associated with the lack of psychological measures and insufficient attention paid to personality traits that, to a great extent, determine the achievement of exceptional performance. Talent Identification (TI) in team sports requires more sensitive tests for prediction of successful game activity; such an item as fatigue tolerance was not taken into account by training experts and analysts. Main findings. 1. Athletic Talent is a complex, multifaceted phenomenon that is widely considered from methodological, biological, philosophical and social positions; 2. The methodological foundation can be considered the basic background for general comprehension of the problem and fulfilment of various scientific and practical projects directed towards the recognition, identification and promotion of talented individuals.